Analisis Kinerja OpenFlow Switch Aruba 2920 - Zefanya Hermanta; Widhi Yahya; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
OpenFlow switches are network switches based on the OpenFlow protocol in forwarding packets on an SDN network. The various switch vendors have provided OpenFlow-enabled networks to support various versions of the OpenFlow protocol. In the implementation of switch there are capacity limitations of TCAM on line-speed forwarding and only accommodate a limited number of streams. Therefore, it will produce different performance. In this study, the authors conducted an analysis of performance OpenFlow switch Aruba 2920. In addition, it uses the emulator mininet as a reference for comparing network performance. The test results show that the system can search several paths in the network topology and along with the path formation time or referred to as convergance time. Tests show that throughput and packet loss on multi-path routing produce better performance, but convergence time is slightly longer than single-path routing. The resulting performance on the Aruba 2920 OpenFlow switch network is very low compared to the emulator mininet, because there are limitations to the group table type select and thrash packet headers on the hardware table so that the flow table is managed in software table.